Case Report: The Application of Dupilumab in Atopic Dermatitis Children Complicated With Nephrotic Syndrome - Yang, Ya-Qi; Chen, Hao; Qiu, Li-Ru; Zhu, Rong-Fei (Frontiers in Medicine, 2022)
Nephrotic syndrome (NS) tends to be more common in patients with history of allergies. Atopic dermatitis (AD) is one of the most common allergic diseases in children. Dupilumab, a dual IL-4 and IL-13 inhibitor, has been widely used to treat AD patients. However, the efficacy and safety of Dupilumab in NS is unclear. We reported two AD patients with NS comorbidities treated with Dupilumab. The outcomes showed the good control of NS and less systemic steroids and/or immunosuppressive agents use during the Dupilumab treatment period, accompanied by significant relief of AD symptoms. We suggest prospective pilot studies and randomized controlled trials could be carried out to validate the efficacy and safety of Dupilumab in the treatment of NS patients.